SOSIALISASI BAHAYA GAWAI DAN TAMAN EDUKATIF SABAGAI UPAYA MENGURANGI KECANDUAN GAWAI PADA ANAK SEKOLAH DASAR DI SDN BUNULREJO 04 KOTA MALANG - Anwar, Moh. Farid Nurul; Sugiharto, Friesta Bagus; Rifa’I, Muhamad (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2023)
Gadget addiction in children has increased since the COVID-19 pandemic. The transition to normal times after the COVID-19 pandemic has made it difficult for children to switch from the habit of using devices, causing laziness for school. This encourages efforts to divert children's habits in using devices. SDN Bunulrejo 04 is one of the schools in Malang which is located at Jl. Warinoi No. 20, Bunulrejo, Blimbing. This school is one of the schools that currently conducts face-to-face learning. The number of complaints from parents about their children who are addicted to gadgets is a problem that needs to be overcome. The problem of device addiction needs to be resolved to minimize the effects of device use on children. The proposer and partners will seek steps to divert children's tendency towards devices with fun play alternatives at school so as to encourage children to be diligent and miss school. The solution offered to solve the problem at SDN Bunulrejo 04 is the creation of an educational park that facilitates children to play while learning so as to create a fun play environment so that children miss school. The expected outcome of this solution is the creation of an educational park so that it can reduce device addiction in children and the return of children's enthusiasm for face-to-face schooling which in turn can improve children's learning outcomes at SDN Bunulrejo 04.